Destination image perceived by domestic tourists: The influence of Generation Gap - Seabra, Cláudia (2020)
The first type of tourism was essentially domestic. However, tourist activities have become a major trend lately, particularly in some locations. According to UNWTO (2016), domestic tourism involves an estimated volume of 5 to 6 billion tourists across the whole world. As a result, some destinations consider it imperative to promote and develop domestic tourism, since it represents an important input to local and national economy. Notwithstanding these facts, most actions taken and research conducted focus on international tourists. An empirical study involving 622 domestic tourists reveals that the main cognitive destination image dimensions are Simplicity and Authenticity, Good Environment, Relaxation and Socialization, Good Infrastructures, Nostalgia and History and Culture. Regarding the affective attributes, most tourists in the sample have strong positive feelings regarding the visited destination. In addition, results prove that those tourists’ generational differences influence the way they build the cognitive and affective images of a certain destination. The discussion focuses on the kind of implications tourism destinations may have for Management and Marketing.